Analysis of the efficiency of recombinant Escherichia coli strain cultivation in a gas‐vortex bioreactor. (8th March 2017) - Savelyeva, Anna V.; Nemudraya, Anna A.; Podgornyi, Vladimir F.; Laburkina, Nadezhda V.; Ramazanov, Yuriy A.; Repkov, Andrey P.; Kuligina, Elena V.; Richter, Vladimir A.
Abstract: The levels of aeration and mass transfer are critical parameters required for an efficient aerobic bioprocess, and directly depend on the design features of exploited bioreactors. A novel apparatus, using gas vortex for aeration and mass transfer processes, was constructed in the Center of Vortex Technologies (Novosibirsk, Russia). In this paper, we compared the efficiency of recombinant Escherichia coli strain cultivation using novel gas‐vortex technology with conventional bioprocess technologies such as shake flasks and bioreactors with mechanical stirrers. We demonstrated that the system of aeration and agitation used in gas‐vortex bioreactors provides 3.6 times higher volumetric oxygen transfer coefficient in comparison with mechanical bioreactor. The use of gas‐vortex bioreactor for recombinant E. coli strain cultivation allows to increase the efficiency of target protein expression at 2.2 times for BL21(DE3)/pFK2 strain and at 3.5 times for auxotrophic C600/pRT strain (in comparison with stirred bioreactor).